Insights on the Socio-Economic Impacts of Research Misconduct - Rodrigues, Rowena; Pizzolato, Daniel (Public Governance, Administration and Finances Law Review, 2024)
Research misconduct (RM) and questionable research practices (QRPs) have a considerable impact on researchers, economy and society. Using a socio-economic impact assessment methodology, this article identifies and assesses their impacts. The objective is to help support the measures developed to promote research ethics and research integrity principles through shared responsibility (individual and institutional) and improve education and training. The article presents recommendations for policy and future research as part of a cohesive framework that takes socio-economic impacts into account. This qualitative study advances and updates current knowledge on the impacts of RM, enriching existing research by introducing new insights, especially regarding socio-economic dimensions, affected stakeholders, and the relevance and significance of these impacts.